Capabilities of the RENEB network for research and large scale radiological and nuclear emergency situations. (2nd January 2017) - Monteiro Gil, Octávia; Vaz, Pedro; Romm, Horst; De Angelis, Cinzia; Antunes, Ana Catarina; Barquinero, Joan-Francesc; Beinke, Christina; Bortolin, Emanuela; Burbidge, Christopher Ian; Cucu, Alexandra; Della Monaca, Sara; Domene, Mercedes Moreno; et al.
Abstract: Purpose: To identify and assess, among the participants in the RENEB (Realizing the European Network of Biodosimetry) project, the emergency preparedness, response capabilities and resources that can be deployed in the event of a radiological or nuclear accident/incident affecting a large number of individuals. These capabilities include available biodosimetry techniques, infrastructure, human resources (existing trained staff), financial and organizational resources (including the role of national contact points and their articulation with other stakeholders in emergency response) as well as robust quality control/assurance systems. Materials and methods: A survey was prepared and sent to the RENEB partners in order to acquire information about the existing, operational techniques and infrastructure in the laboratories of the different RENEB countries and to assess the capacity of response in the event of radiological or nuclear accident involving mass casualties. The survey focused on several main areas: laboratory's general information, country and staff involved in biological and physical dosimetry; retrospective assays used, the number of assays available per laboratory and other information related to biodosimetry and emergency preparedness. Following technical intercomparisons amongst RENEB members, an update of the survey was performed one year later concerning the staff and the available assays. Conclusions: The analysis of RENEB questionnaires allowed a detailed assessment of existing capacity of the RENEB network to respond to nuclear and radiological emergencies. This highlighted the key importance of international cooperation in order to guarantee an effective and timely response in the event of radiological or nuclear accidents involving a considerable number of casualties. The deployment of the scientific and technical capabilities existing within the RENEB network members seems mandatory, to help other countries with less or no capacity for biological or physical dosimetry, or countries overwhelmed in case of a radiological or nuclear accident involving a large number of individuals.